Analysis of Hydro-Sedimentary Processes in the El-Malah East River Basin Upstream of the Beni Slimane Gauging Station (N Algeria) - FREDJ, Amira; GHERNAOUT, Redhouane; DAHMANI, Saad; REMINI, Boualem (GeoScience Engineering, 2023)
Predicting suspended sediment load is essential to identify its intensity and define necessary actions for its reduction. Mathematical models simulating suspended sediment load are an interesting tool for this purpose. The methodological approach adopted in this article consists in looking for a regressive model that can better explain the suspended sediment discharge through flow discharge by studying this relationship at different temporal scales. The work comprises analyzing and quantifying the suspended sediment intakes conveyed by the El-Malah East river at the Beni Slimane gauging station towards the Koudiat Acerdoune reservoir. The available data covers the period from 1973/74 to 1988/1989 for instantaneous measurements of liquid flow discharge Ql – Suspended sediment concentration C and the period from 1985/86 to 1996/97 for daily mean flow discharges and daily mean precipitations. Only power relations obtained on a seasonal scale giving the best coefficient of determination have been selected for the quantification of suspended sediment load conveyed by El-Malah river at Beni Slimane hydrometric station in the period of availability of daily mean flow discharges (1985/86 to 1996/97). The optimization of suspended sediment rating curves has been validated by comparison of the estimated values ​​with the ​​observed data and by fitting Normal distribution to residues datasets. The use of these models has highlighted an intra-annual distribution of the suspended sediment contributions conveyed by the El-Malah East river at Beni Slimane hydrometric station estimated at 0.088 Mt per year, representing a specific degradation of about 325 t.km-2y-1 (423 t.km-2y-1 of suspended and bed loads). The results have also shown that the highest liquid intake occurs in spring (45.72 %), winter (32.36 %) and autumn (11.93 %) seasons. This distribution, as well as the distribution of the monthly rainfalls, allowed the conclusion that the runoff period does not always correspond to the rainy period. The highest precipitation occurs in winter (38.74 %), spring (32.25 %) and autumn (21.53 %) seasons. The intra-annual distribution of suspended sediment contributions showed that winter and autumn participate in each one with 28.31 and 27.03% of the total suspended sediment load annually, while summer and spring participate with 23.28 and 21.38 %, respectively. The obtained results can be verified and improved by increasing the size of the available series. They provide appreciable elements of comparison for others basins of the same order, located in semi-arid and arid regions and subjected to similar phenomena. They also allow river basin managers and policymakers to consider necessary actions to fight against land erosion, preserve human activities, increase the life of the Koudiet Acerdoune dam 60 km downstream from the watershed outlet, facilitate decision-making and planning, and ensure effective management. Keywords: Rating curve; Regression; Residues; Surface degradation; Surface runoff; Suspended sediment load.